Expression of cyclin H in normal and cancerous endometrium, its correlation with other cyclins, and association with clinicopathologic parameters. Issue 1 (1st January 2006) - Kayaselcuk, F.; Erkanli, S.; Bolat, F.; Seydaoglu, G.; Kuscu, E.; Demirhan, B.
Abstract : Cyclins are known as regulatory proteins in cell cycle. Cyclin H is a part of cyclin H/Cdk7/Mat1 complex, which is necessary for cellular proliferation. This study was designed to investigate the correlation of cyclin H expression with tumorigenesis of the endometrium and clinicopathologic variables. Immunohistochemical staining using labeled streptavidin–biotin complex was performed on formalin-fixed, paraffin-embedded endometrial tissues of the proliferative, hyperplastic, and carcinomatous types. Immunostaining for cyclins A, B1, D1, D3, E, H, and cyclin dependent kinase 2 were evaluated. The expression of cyclins A, D1, D3, and H in hyperplasia was significantly more frequent than those of proliferative phase and less than those of endometrioid adenocarcinoma. The expression of cyclin H was correlated with lymphvascular space invasion and clinical stage in carcinoma but not with myometrial invasion, lymph node metastasis, and menopause status. The expression of cyclin H could be involved in the transformation of the endometrium into malignancy and might be a marker for more proliferative and malignant features. It might be one of the biomarkers for determining proliferative activity in endometrial hyperplasia and endometrioid adenocarcinoma.